Penyalahgunaan Rekening yang Tertaut di Nomor Handphone dalam Perspektif Cyber Crime - Ni Ketut Sugi Harta Nadi Agustina Putri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Misuse of accounts linked to telephone numbers has become a serious issue in the realm of cybercrime. This often happens when a user's telephone number is inactive or has entered a grace period, and is then resold by the provider to a third party. This creates an opening for hackers to access accounts associated with that number, including banking and e-commerce accounts. By utilizing the information obtained, hackers can carry out illegal transactions that harm genuine users. This article was created to analysis the mechanisms of abuse in the context of cybercrime, as well as the psychological and financial impacts experienced by victims. The results of this case analysis show that a lack of awareness of cyber security and personal data protection increases the risk of misuse, making it important for users to implement stricter security measures.